2014
DOI: 10.1152/ajpcell.00132.2014
|View full text |Cite
|
Sign up to set email alerts
|

Serum starvation regulates E-cadherin upregulation via activation of c-Src in non-small-cell lung cancer A549 cells

Abstract: . Serum starvation regulates E-cadherin upregulation via activation of c-Src in non-small-cell lung cancer A549 cells. Am J Physiol Cell Physiol 307: C893-C899, 2014. First published August 27, 2014 doi:10.1152/ajpcell.00132.2014.-E-cadherin is essential for the integrity of adherens junctions between lung epithelial cells, and the loss of E-cadherin allows cell motility and is thought to promote lung cancer metastasis. While the downregulation of E-cadherin expression has been well characterized and is seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 55 publications
(63 reference statements)
3
20
0
Order By: Relevance
“…Down-regulation of E-cadherin expression has been well studied, but few reports have focused on up-regulation of E-cadherin. We have shown that Src kinase up-regulates E-cadherin translation in A549 cells (51). Here, we present evidence that USP48 depletion increases E-cadherin mRNA levels in epithelial cells.…”
Section: Discussionsupporting
confidence: 53%
“…Down-regulation of E-cadherin expression has been well studied, but few reports have focused on up-regulation of E-cadherin. We have shown that Src kinase up-regulates E-cadherin translation in A549 cells (51). Here, we present evidence that USP48 depletion increases E-cadherin mRNA levels in epithelial cells.…”
Section: Discussionsupporting
confidence: 53%
“…Although it is rarely reported that starvation can increase the E-cadherin of PCa cells PC3 and DU145. However, similar reports have been found in other cancer cell studies [33]. Silencing Akt1 suppresses the increased of E-cadherin caused by starvation.…”
Section: Discussionsupporting
confidence: 88%
“…Dong et al [38] demonstrated, through in vitro studies using A549 non-small cell lung cancer cell lines, that serum starvation increases E-cadherin expression. E-cadherin is involved in the pathobiology of several types of cancer: the loss or dysfunction of E-cadherin is associated with increased lung cancer cell proliferation and invasiveness [39].…”
Section: Dietary Restriction-induced Molecular Changesmentioning
confidence: 99%